Terahertz photoconductivity of graphene nanostructures - Jensen, Søren A.; Ulbricht, Ronald; Narita, Akimitsu; Feng, Xinliang; Müllen, Klaus; Turchinovich, Dmitry; Hertel, Tobias; Bonn, Mischa (International Conference on Infrared, Millimeter, and Terahertz Waves, IRMMW-THz, 2013)
The photoconductive properties of graphene nanoribbons and carbon nanotubes were studied using optical pump-THz probe spectroscopy. A reduction in conductivity of GNRs compared to CNTs was observed. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-20